PENGARUH ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DISCLOSURE TERHADAP KINERJA PERUSAHAAN - Maulida Nur Safriani; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2020)
This study aims to discuss the effect of Environmental, Social, Governance (ESG) disclosure on firm performance, using control variable such as financial leverage and total assets. The variables used in this study are the dependent variable (operational performance, financial performance, and market performance), the independent variable (ESG disclosure), and control variables (financial leverage and total assets). The population in this study is non financial companies listed on the Indonesia Stock Exchange in 2015-2018. Sampling is done by purposive sampling. Based on the purposive sampling method, samples obtained were 44 companies for the four years obtained (2015-2018). The analytical method used in this study is multiple regression analysis. In addition, the statistical technique used to test the hypotheses proposed in this study is panel data. The results of this study indicate that ESG disclosure have a positive and significant effect on operational and financial performance, while ESG disclosure haven’t a positive and significant effect on market performance.